Socioeconomic Status and Foodborne Pathogens in Connecticut, USA, 2000–2011 - Bridget M. Whitney; Christina Mainero; Elizabeth Humes; Sharon Hurd; Linda Niccolai; James L. Hadler (Emerging Infectious Diseases, 2015)
Foodborne pathogens cause >9 million illnesses annually. Food safety efforts address the entire food chain, but an essential strategy for preventing foodborne disease is educating consumers and food preparers. To better understand the epidemiology of foodborne disease and to direct prevention efforts, we examined incidence of Salmonella infection, Shiga toxin–producing Escherichia coli infection, and hemolytic uremic syndrome by census tract–level socioeconomic status (SES) in the Connecticut Foodborne Diseases Active Surveillance Network site for 2000–2011. Addresses of case-patients were geocoded to census tracts and linked to census tract–level SES data. Higher census tract–level SES was associated with Shiga toxin–producing Escherichia coli, regardless of serotype; hemolytic uremic syndrome; salmonellosis in persons ≥5 years of age; and some Salmonella serotypes. A reverse association was found for salmonellosis in children <5 years of age and for 1 Salmonella serotype. These findings will inform education and prevention efforts as well as further research.